Model Hidrodinamika Pasang Surut di Perairan Pesisir Barat Kabupaten Badung, Bali - Made Narayana Adibhusana; I Gede Hendrawan; I Wayan Gede Astawa Karang (Fakultas Kelautan dan Perikanan Universitas Udayana, 2016)
Finite Volume Coastal Ocean Model (FVCOM) is using for numerical modeling of hydrodynamic tidal water in west coast of Badung regency, Bali. The model result is validation with field observations data in the area using the equation Root Mean Square Error (RMSE). Field tidal data elevation of sea level elevation measurements were obtained by using the palm of tidal. Field data speed and direction of sea currents obtained using Lagrangian method. Excellent results obtained with RMSE values tidal elevation of sea level by 0.24 m dan RMSE values for sea current is 0.125 m/s. The results of model simulations show sea current patterns in the waters of the west coast of Badung regency, Bali relatively the same at the spring tide and neap tide conditions. The pattern of sea currents at high tide shows current vector that moves in toward the water of the west coast of Badung regency area from Bali Strait and the Indian Ocean. At the time of low tide sea current vector movement towards Bali Strait and the India Ocean. Sea current velocity in the eastern waters of the west coast of Badung regency (longitude of 115,05°– 115,17°) is higher than the sea current velocity in western waters area (longitude of 114,95°– 115,05°). Sea current velocity in the waters of the west coast of Badung regency on the condition of the spring tide range from 0.005 to 0.025 m/s, on the other side the sea current velocity on the neap tide conditions range from 0.005 to 0.012 m/s.